Tindakan Pencegahan Masyarakat terhadap Kejadian Malaria di Wilayah Kerja Puskesmas Tikala Kota Manado - Kaawoan, Keren; Rombot, Dina V.; Palandeng, Henry M. F. (UNIVERSITAS SAM RATULANGI, 2016)
Background: According to the World Malaria Report (2015) by the World Health Organization (WHO), the number of malaria cases in the world declined from 262 million in 2000 (range : 205-316 million) , to 214 million in 2015 (range : 149-303 million) a decrease of 18% . Most cases in 2015 is estimated to occur in the WHO African Region (88%), followed by the South-East Asia Region (10%) and the Eastern Mediterranean Region (2%). The incidence of malaria , which also takes into account population growth, estimated to have declined 37% in the period 2000-2015. Altogether 57 of the 106 countries that previously had a transmission running in 2000 has been able to reduce malaria incidence >75%. More far 18 countries have been estimated to reduce the incidence of malaria by 50-75%. Manado city recorded a number of suspected malaria in 2014 amounted to 1,361 and from 780 people blood sample examined 107 people were found positive as the result. According to available data, the Tikala District always be at the top of the donation morbidity of malaria. This research aim to find whether there is a relationship between community preventive measures with malaria incidence. Methods: The research design used in this study is ananalytic, using cross-sectional study. The data analysis was done manually and by computer for chi-square test. Result and Conclusion: The results of data processing usingchi-square test showed that there was no significant correlation between the incidence of malaria and society precautions p= 0,37(p>0.05). This result suggested that education about malaria and its preventive measures by health center could be improved, as well as the thorough treatment against Plasmodium parasite that infected patients.